Analysis of depression status and nursing interventions in 163 patients with liver disease (163例肝病患者抑郁状况调查及护理干预效果分析) - WANG Yundan (望运丹); WANG Weixian (王伟仙); HU Deying (胡德英); LIU Yilan (刘义兰) (中西医结合护理)
Objective The 9-item Patient Health Questionnaire (PHQ-9) was used to screen the depression status of inpatients with liver disease in the Infection Department of a grade A hospital, and nursing interventions were taken for patients with moderate and severe depression during hospitalization, so as to reduce the depression of patients with liver disease during hospitalization and promote their mental health and rehabilitation. Methods Using PHQ-9 for depression screening, 163 hospitalized patients with liver diseases in the Infection Department were evaluated from August 1, 2021 to December 31, 2021, and the data were analyzed. According to the results of PHQ-9 depression screening scale, patients with moderate and severe liver disease depression were given 15 days of nursing interventions. Results The results showed that there were 63 (38. 65%)patients with depression, of which 39(61. 90%) cases of mild depression, 15(23. 81%) cases of moderate depression, 7(11. 11%)cases of moderate to severe depression, and 2(3. 17%)cases of severe depression. Items with high total score included: Item ④: Feeling tired or lack of energy; Item③: Difficulty falling asleep, restless sleep or excessive sleep; Item①: Not feeling energetic or interested in doing things; Item⑤: Loss of appetite or eating too much. After implementation of nursing interventions, 3 patients with moderate-to-severe depressive liver disease were identified as been mildly depressed, 4 patients with moderate-to-severe depression and 2 patients with severe depression were identified as been moderately depressed. Conclusion The depression status of inpatients with liver disease is associated with to the treatment and rehabilitation of the patient during hospitalization, and also seriously affects the physical and mental health of patients, which needs to be paid attention to by all medical workers. The screening scale has positive significance for screening patients with depression due to liver disease, and nursing intervention measures for patients with moderate to severe and severe depression due to liver disease have achieved certain results. (目的 通过PHQ-9抑郁筛查量表对某三级甲等医院感染科肝病住院患者入院时的抑郁状况进行筛查, 并在住院期间对中重度及重度抑郁的肝病患者采取护理干预, 以缓解住院期间肝病患者的抑郁情绪, 促进患者心理健康及疾病康复。方法 2021年8月—12月, 采用PHQ-9抑郁筛查量表对某三级甲等医院感染科163例肝病住院患者进行入院评估, 并进行数据分析, 根据PHQ-9抑郁筛查量表结果对中重度及重度肝病抑郁患者采取为期15 d的护理干预。结果 筛查结果显示, 抑郁症状患者63(38. 65%)例, 其中轻度抑郁39(61. 90%)例, 中度抑郁15(23. 81%)例, 中重度抑郁7(11. 11%)例, 重度抑郁2(3. 17%)例。总得分较高的条目包括: 条目④感觉疲惫或没有活力; 条目③入睡困难、睡不安稳或者睡眠过多; 条目①做事时提不起劲或没有兴趣; 条目⑤食欲不振或吃太多。经15 d的护理干预后, 3例中重度抑郁患者变为轻度抑郁, 4例中重度抑郁患者及2例重度抑郁患者变为中度抑郁。结论 医院感染科肝病住院患者入院时的抑郁状况关系到患者住院期间的治疗与康复效果, 也严重影响患者的身心健康, 需引起全体医护工作者的重视。科室采用PHQ-9抑郁筛查量表对筛查肝病抑郁患者有积极意义, 针对中重度及重度肝病抑郁患者采取的护理干预措施达到了一定的效果。)